2004
DOI: 10.1074/jbc.m312760200
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase II-mediated Phosphorylation Regulates α-Synuclein/Synphilin-1 Interaction and Inclusion Body Formation

Abstract: ␣-Synuclein is a phosphoprotein that accumulates as a major component of Lewy bodies in the brains of patients with Parkinson disease. Synphilin-1, which is also present in Lewy bodies, binds with ␣-synuclein and forms cytoplasmic inclusions in transfected cells. Yet the molecular determinants of this protein-protein interaction are unknown. Here we report that casein kinase II (CKII) phosphorylates synphilin-1 and that the ␤ subunit of this enzyme complex binds to synphilin-1. Additionally, both CKII ␣ and ␤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 39 publications
8
79
2
Order By: Relevance
“…Our data now suggest that the modulation of inclusion body formation also depends on GSK3␤ phosphorylation. Recently, Mouradian and co-workers found that casein kinase II phosphorylation at a still unidentified region of synphilin-1 is required for synphilin-1/␣-synuclein aggregation (29). Under our experimental conditions, casein kinase II inhibitor had no effect on synphilin-1 ubiquitylation or its ability to form cytosolic aggregates with SIAH-1.…”
Section: Discussionmentioning
confidence: 59%
“…Our data now suggest that the modulation of inclusion body formation also depends on GSK3␤ phosphorylation. Recently, Mouradian and co-workers found that casein kinase II phosphorylation at a still unidentified region of synphilin-1 is required for synphilin-1/␣-synuclein aggregation (29). Under our experimental conditions, casein kinase II inhibitor had no effect on synphilin-1 ubiquitylation or its ability to form cytosolic aggregates with SIAH-1.…”
Section: Discussionmentioning
confidence: 59%
“…We reported previously that synphilin-1, a protein that interacts with ␣-synuclein (Engelender et al, 1999), is highly enriched in Lewy bodies (Wakabayashi et al, 2000). Cotransfection of ␣-synuclein and synphilin-1 in human embryonic kidney 293 (HEK 293) cells yields cytoplasmic eosinophilic inclusions resembling Lewy bodies (Engelender et al, 1999;Lee et al, 2004). We also identified synphilin-1 as a substrate of parkin (a ubiquitin ligase, also present in Lewy bodies) (Chung et al, 2001a;Shimura et al, 2001;Schlossmacher et al, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…Therefore, it is reasonable to predict that the identification of factors that regulate the physical and functional interactions between ␣-synuclein and synphilin-1 will help to uncover the molecular etiology of LB formation and PD pathogenesis. CKII has been recently reported as a potent kinase that phosphorylates both ␣-synuclein and synphilin-1 and regulates the binding between these two proteins (11,31). Significantly, the CKII inhibitor, DRB, abolishes this interaction and reduces inclusion body formation in cell cultures (31).…”
Section: Discussionmentioning
confidence: 99%
“…Pin1 Promotes the Interaction of ␣-Synuclein with Synphilin-1-We next addressed whether Pin1 expression affects the interaction between ␣-synuclein and synphilin-1, because this binding is crucial for the formation of cytoplasmic inclusions (9,31). 293T cells were transfected with HA-␣-synuclein and Xpress-synphilin-1, in the presence or absence of exogenous Pin1 co-expression, and lysates were subjected to immunoprecipitation with anti-Xpress antibodies.…”
Section: Pin1 Accumulates In the Lewy Bodies Of Parkinson Disease-mentioning
confidence: 99%